Orientación de Pasajeros con Discapacidad Visual dentro del Sistema de Transporte Masivo Transmilenio, mediante Geolocalización Satelital - Camargo, Julián; González, Luis; Segura, Diego; Garay, Fabian; Rincón, Nubia (Ingeniería, 2017)
Context: Although the mass-transport system Transmilenio provides audio information for travelers’ guidance, this is not helpful enough to blind users who are not able to transit easily within the system. For these reason, portable guidance devices are needed to improve the level of autonomy of the visually impaired people while using the transport system. Method: A review of aid devices to improve the level of autonomy of people with visual impairment was conducted so as to define the most practical technology for building an affordable device usable in the city of Bogotá. Subsequently, the functional modules of the device were defined, including file storage, sound reproduction, user interface and satellite geolocalization and location. Once built, the operation of the device was tested with 10 volunteers in condition of visual impairment who were oriented with the device between two main stations of one Transmilenio line; a final statistical study was conducted on the operation and usability perception of the device by the users. Results: 100% of the users were able to reach their destination successfully in the pilot test. In regards to the usability perception, users highlighted features such as sound indications for setting the device and orientation guidance throughout the journey. On the other hand, one of the main difficulties found was to correctly identify the bus approaching the stop and similarly locating the corresponding boarding door, as multiple bus routes may alight in the same door. Conclusions: The device was built incorporating low-cost technologies intended to make it affordable in an eventual mass—scale production. Likewise, a discreet design was chosen so as to lessen the risk of robbery, which unfortunately is a frequent issue in the Transmilenio system due to overcrowding of buses and stations. Additionally, we remark that the prototype can be made smaller by using special—purpose circuit boards. Policy-makers may take into account these considerations for an eventual wide implementation as part of governments’ plans for mobility inclusion in mass-transport systems for disabled people, in comparison with other alternatives such as smart cell phones Language: Spanish.